Solve -3( x – 1 ) + 8 ( x – 3 ) = 6x + 7 – 5x

Question

Solve -3( x – 1 ) + 8 ( x – 3 ) = 6x + 7 – 5x

in progress 0
Eliza 3 weeks 2021-09-23T11:41:07+00:00 2 Answers 0

Answers ( )

    0
    2021-09-23T11:42:14+00:00

    x = 7
    -3(x-1)+8(x-3)=6x+7-5x
    (distribute)
    -3x+3+8x-24=6x+7-5x
    (combine like terms)
    5x-21=x+7
    (subtract)
    4x-21=7
    (add)
    4x=28
    (divide)
    x=7

    0
    2021-09-23T11:43:03+00:00

    Answer:

    x=3

    Step-by-step explanation:

    -3( x – 1 ) + 8 ( x – 3 ) = 6x + 7 – 5x

    -3x+3+8x-24=6x+7-5x

    5x-19=x+7

    4x=12

    x=3

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )